Problems of the adoption of the Euro in Poland and the Baltic countries - Gediminas Davulis; Linas Šadžius (Torun Business Review, 2011)
The possibilities of Poland, Latvia and Lithuania to adopt the euro, which is one of most important task of the economic policy in these countries is analyzed in the article. The international importance of the euro, the advantages and disadvantages of the single currency are discussed. Experience of Germany in adopting of the euro is analyzed. The strategy of the adoption of the euro in Lithuania is presented. The analysis based on the data of Eurostat database shows that Poland is the country with most possibilities to adopt the euro. However both Lithuania and Latvia may become the euro zone member states, too, if they firstly will cope with financial problems of the government and will revitalise and develop their internal market.